2011
DOI: 10.1016/j.tripleo.2011.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the immunohistochemical expression of collagen IV, MMP-9, and TIMP-2 in odontogenic cysts and tumors

Abstract: Objective. The aim of this study was to evaluate the immunohistochemical expression of collagen IV, matrix metalloproteinase (MMP) 9 and tissue inhibitor of MMP (TIMP) 2 in dentigerous cysts (DCs), radicular cysts (RCs), keratocystic odontogenic tumors (KOTs), and ameloblastomas. Study design. Twenty cases of DCs, 20 RCs, 20 KOTs, and 20 ameloblastomas were selected and analyzed by immunohistochemistry. Results. Most DCs and RCs showed continuous and Ͼ50% staining for collagen IV in the basement membrane of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 34 publications
5
46
0
3
Order By: Relevance
“…This is in accordance with the result of Henriques et al [22] that found 95 % of ameloblastoma having positive MMP-9 immunoreactions. Most of our specimens show moderate to strong expression intensity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the result of Henriques et al [22] that found 95 % of ameloblastoma having positive MMP-9 immunoreactions. Most of our specimens show moderate to strong expression intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Study has shown that MMP-9 is produced by osteoclast in the human bone tissues and suggest that it can degrade bone collagens in concert with MMP-1 and cysteine proteinases in the subosteoclastic microenvironment [16]. Several studies have been conducted to analyze the MMP-9 expression in ameloblastoma [8,[12][13][14][20][21][22]. MMP-9 expression in ameloblastoma is higher than in other odontogenic cysts and keratocyst odontogenic tumor (KOT).…”
Section: Discussionmentioning
confidence: 99%
“…The developmental mechanisms of these odontogenic lesions may be related to MMP expression (28). Increased expression of MMP-9 in KOTs compared to other odontogenic cysts has been demonstrated by previous studies (28)(29)(30). Our results showed significantly higherMMP-l and -9 expression in KOTs compared to RCs and DCs, while there was no significant difference in MMP -1 and -9 expression between KOTs andABLs.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, it is necessary to further elucidate other effects of COX-2 in the epithelium and connective tissue of odontogenic lesions and to compare dentigerous cyst with ameloblastoma. Previous studies have shown that each of ameloblastoma and dentigerous cyst presents a distinct evolution and biological behavior, and in addition to their clinical and behavioral differences (57), they reflect diversities in various features such as gene expression (58), pattern of expression of cytokines (3), interaction of different proteins, and collagen components (57).…”
Section: A B C D E F G Hmentioning
confidence: 99%